2020
DOI: 10.14500/aro.10724
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Profile and Antimicrobial Susceptibility of Isolates Recovered from Lower Respiratory Tract Infection for Patients in Rizgary Hospital, Erbil

Abstract: Recognition of etiologies of lower respiratory tract infection (LRTI) may help in delivering effective treatment options and circumvent emergence of antibiotic resistance. This study was carried out to uncover bacterial profile and antibiotic sensitivity patterns among 310 LRTI patients attended Rizagary Hospital between January 2014 to December 2016. Standard laboratory techniques were applied in collecting, processing, and culturing sputum and bronchial wash specimens. VITEK® 2 compact systems were used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…These results indicate that multidrug-resistant (MDR) bacteria were associated with the identified pathogens and may play a negative role in chronic wound infection. These findings come in agreement with previous studies of ours that confirmed the existence of MDR bacteria among patients identified with urinary tract and lower respiratory tract infections (Al-Naqshbandi, et al, 2019;Chawsheen, et al, 2020;Abbas and Owaid, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…These results indicate that multidrug-resistant (MDR) bacteria were associated with the identified pathogens and may play a negative role in chronic wound infection. These findings come in agreement with previous studies of ours that confirmed the existence of MDR bacteria among patients identified with urinary tract and lower respiratory tract infections (Al-Naqshbandi, et al, 2019;Chawsheen, et al, 2020;Abbas and Owaid, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…We used AMP in our experiments because typically, it is effective against both GPB and GNB. Unfortunately, there is growing evidence suggesting that AMP globally become less effective nowadays in eradicating different types of pathogenic bacteria, which is mainly due to the emergence of AMR in these bacteria as a consequence of excessive use of this drug (Katzung and Trevor, 2012;Krzyżaniak, Pawłowska and Bajorek, 2016;Chawsheen, AL-Naqshbandi and Abdulqader, 2020;Al-Naqshbandi, et al, 2021). In our experiments, bacteria were treated with Ag NPs, AMP, and their combinations.…”
Section: Discussionmentioning
confidence: 99%